The downregulation of HSP90‐controlled CRALBP expression is associated with age‐related vision attenuation. Issue 3 (24th February 2023) - Chen, Dan‐Dan; Liu, Baixue; Wang, Yuxuan; Jiang, Mingjun; Shang, Guohui; Xue, Mengjiao; Jia, Xiaolin; Lang, YouFei; Zhou, Guiling; Zhang, Fengyan; Peng, Xuyan; Hu, Yanzhong
Abstract: The dysfunction of CRALBP, a key regulator of the visual cycle, is associated with retinitis punctata albescens characterized by night vision loss and retinal degeneration. In this paper, we find that the expression of CRALBP is regulated by heat shock protein 90 (HSP90). Inhibition of HSP90α or HSP90β expression by using the CRISPR‐Cas9 technology downregulates CRALBP's mRNA and protein expression in ARPE‐19 cells by triggering the degradation of transcription factor SP1 in the ubiquitin–proteasome pathway. SP1 can bind to CRALBP's promoter, and inhibition of SP1 by its inhibitor plicamycin or siRNA downregulates CRALBP's mRNA expression. In the zebrafish, inhibition of HSP90 by the intraperitoneal injection of IPI504 reduces the thickness of the retinal outer nuclear layer and Rlbp1b mRNA expression. Interestingly, the expression of HSP90, SP1, and CRALBP is correlatedly downregulated in the senescent ARPE‐19 and Pig primary RPE cells in vitro and in the aged zebrafish and mouse retinal tissues in vivo. The aged mice exhibit the low night adaption activity. Taken together, these data indicate that the HSP90‐SP1 is a novel regulatory axis of CRALBP transcriptional expression in RPE cells. The age‐mediated downregulation of the HSP90‐SP1‐CRALBP axis is a potential etiology for the night vision reduction in senior people. Abstract : The function of visual cycle is attenuated in the seniors. Dysfunction of CRALBP is associated with nyctalopia and AMD. Both Hsp90α and HSP90β participate in regulating CRALBP transcriptional expression by modulating SP1 protein stability. HSP90 and CRALBP are correlatedly downregulated in the senescent RPE cells in vitro and in vivo. These data uncover that the age‐mediated downregulation of the HSP90‐SP1‐CRALBP axis is a potential etiology for the night vision reduction in senior people.